Relación entre el conocimiento docente de los estilos parentales de socialización y el manejo técnico pedagógico de las habilidades de convivencia escolar de los niños/as de 5 años de las I.E de la ciudad de Rioja - Romero Nava, Magna Belinda (2014)
The formation process of the human being is a complex and continuous succession of events aimed at modifying its behavior, in which the social dimension presents more nuanced and difficult, becoming an educational challenge that must elucidate and properly manage the level of early childhood education as a starting point for understanding the variables involved. Our research is focused on the initial level educational institutions of the city of Rioja in arder to analyze and describe the knowledge that teachers possess this level of parental socialization styles of children five years of age. formative share family from which consistent with the technical management of educational strategies aimed at conditioning the students to their new living environment, wider and more demanding. Based on theoretical contributions that clarify the process of socialization of human beings, taking into account the scientific details of the development of the learner as a social being in the school environment, leads to the understanding of the variables involved in the study that allowed its adequate operational management, providing valuable information for our research. For our research, we welcomed fifteen teachers of educational institutions of the initial level No. 089, No. 287 and No. 288, five in each case, to be considered as the most representative in the city of Rioja. With things proceeded according to the parameters of a descriptive correlational design, having as supports two questionnaires in the same group. Data processing focused on extracting summations, averages and percentages of the observed frequencies in all indicators evaluated, using the calculation of the coefficient called "chi square" to take test the hypothesis whereby it was possible to demonstrate that there a probable significant association between teacher knowledge of parental socialization styles and teaching technical skills management school life of children five years of educational institutions of the initial level of the city of Rioja leve!. This is nothing more than the expression of the insertion of pedagogical random strategies by teachers, since there is no real knowledge of the bases of social behavior internalized within the family, and this inevitably leads to a lack of training consistency.